Cash Management and Performance Small Scale Business in Mbarara City: A Case Study of Central Market. - Nasasira, Naome (Kabale University, 2024)
The study was about the impact of cash management on the performance of small-scale businesses using Mbarara Central Market as a case study. The study addressed the following objectives which included examining the impact of cash management policies on the performance of small-scale businesses, finding out the levels of performance of small-scale businesses, and establishing the relationship between cash management and the performance of small-scale businesses. In chapter two, the existing literature levels on the impact of cash management on the performance of small-scale industries were covered. In chapter three, the researcher described research design, research procedures, methods and data analysis, variables, validity and reliability of the data, instruments, and ethical issues in research. In chapter four, the researcher described the bio-data of the respondents, empirical results basing on the objectively objective. The study was guided by research questions and an interview guide which helped to analyze the situation and arrive at the conclusions and recommendations. During the research study, the designs used were descriptive cross-sectional and explanatory research designs simple uniform, and purposive methods were used. The size used was 30 respondents; the primary total was collected by the use of questionnaires and management reports. From the analysis of findings, the study revealed that cash management has a strong effect on the performance of small-scale businesses. The study concluded that small-scale businesses do not keep proper books of accounts, they use simple exercise books to record their transactions which in turn they do not mind keeping appropriately as most of the businesses are sole proprietorships and can by family members not answer to anybody. The study recommends that small-scale business owner should keep records and books of their daily cash receipts and payments. Small-scale business owners should also adopt a culture of ensuring daily cash safety like banking where even interest can be earned. Techniques to speed up cash collections, like discounts on timely payments, should be ensured to avoid too many receivable accounts and bad debts.